Registries and collaborative studies for primary ciliary dyskinesia in Europe. Issue 2 (26th May 2020) - Ardura-Garcia, Cristina; Goutaki, Myrofora; Carr, Siobhán B.; Crowley, Suzanne; Halbeisen, Florian S.; Nielsen, Kim G.; Pennekamp, Petra; Raidt, Johanna; Thouvenin, Guillaume; Yiallouros, Panayiotis K.; Omran, Heymut; Kuehni, Claudia E.
Primary ciliary dyskinesia (PCD) is a rare inherited disease characterised by malfunctioning cilia leading to a heterogeneous clinical phenotype with many organ systems affected. There is a lack of data on clinical presentation, prognosis and effectiveness of treatments, making it mandatory to improve the scientific evidence base. This article reviews the data resources that are available in Europe for clinical and epidemiological research in PCD, namely established national PCD registries and national cohort studies, plus two large collaborative efforts (the international PCD (iPCD) Cohort and the International PCD Registry), and discusses their strengths, limitations and perspectives. Denmark, Cyprus, Norway and Switzerland have national population-based registries, while England and France conduct multicentre cohort studies. Based on the data contained in these registries, the prevalence of diagnosed PCD is 3–7 per 100 000 in children and 0.2–6 per 100 000 in adults. All registries, together with other studies from Europe and beyond, contribute to the iPCD Cohort, a collaborative study including data from over 4000 PCD patients, and to the International PCD Registry, which is part of the ERN (European Reference Network)-LUNG network. This rich resource of readily available, standardised and contemporaneous data will allow obtaining fast answers to emerging clinical and research questions in PCD. The growing collaborative network of national and international registries and cohort studies of patients with PCD provides an excellent resource for research on this rare disease https://bit.ly/3dto75l